Prophecies of Roman Rule in the Imperial Period (27 BCE–284 CE) - ALaqeel, Munirah Ali Saleh (Journal of Posthumanism, 2024)
This research examines the concept of prophecies and the art of divination in the Roman Empire from 27 BC to 284 AD, highlighting its role as a religious, cultural and political phenomenon. The research aims to analyze how emperors manipulated prophecies to enhance their political legitimacy and guide fateful decisions. In a descriptive-analytic analysis, sources of Roman literature and historiography are considered and analyzed in an attempt to understand the political and religious dimensions of prophecies. Additionally, the study employs comparative analysis to explore the cultural interactions between the Romans and other cultures, including the Greek and Egyptian cultures. The study concluded that prophecies represented not only religious beliefs, but also an effective political tool that helped emperors achieve their goals, especially in times of crises and wars. Additionally, the results revealed that the prophecies reflected the cultural interaction between the Romans and other peoples, and contributed to the formation of the Roman political system. The research recommended the need for deeper comparative studies between prophetic practices in ancient civilizations, with a focus on their role in strengthening political power. It also stressed the importance of a more comprehensive analysis of the primary texts to understand the relationship between religion and politics in the Roman Empire.